2011
DOI: 10.1186/1471-2261-11-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between various measures of obesity and arterial stiffness in morbidly obese patients

Abstract: BackgroundObesity is associated with increased risk of cardiovascular disease. Arterial stiffness assessed by carotid femoral pulse wave velocity (PWV) is an independent predictor of cardiovascular morbidity and mortality. We aimed to investigate how various measures of body composition affect arterial stiffness.MethodsThis is an analysis of cross-sectional baseline data from a controlled clinical trial addressing changes in arterial stiffness after either surgery or lifestyle intervention in a population of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
37
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 45 publications
9
37
2
2
Order By: Relevance
“…In older adults, there are data that indicate increasing arterial stiffness with obesity, [7][8][9] although findings have been inconsistent across studies. [10][11][12][13] In contrast, obese children have reduced arterial stiffness compared with their normal weight peers, [14][15][16] an effect thought to result from physiological adaptation to the hyperemic state of obesity in the young. 16 Taken together these contrasting data from young and old populations suggest age-related differences in the relationship between body composition and arterial stiffness, which have not been fully explored.…”
mentioning
confidence: 99%
“…In older adults, there are data that indicate increasing arterial stiffness with obesity, [7][8][9] although findings have been inconsistent across studies. [10][11][12][13] In contrast, obese children have reduced arterial stiffness compared with their normal weight peers, [14][15][16] an effect thought to result from physiological adaptation to the hyperemic state of obesity in the young. 16 Taken together these contrasting data from young and old populations suggest age-related differences in the relationship between body composition and arterial stiffness, which have not been fully explored.…”
mentioning
confidence: 99%
“…Therefore, the notion of a relationship between the factors of metabolic syndrome and PWV is quite reasonable. However, an interesting finding of previous studies was that this predicted relationship was only observed in women and not in men [13,14]. In particular, the associations between PWV and BMI and HDL were the opposite, while those with BP, FBS, LDL, and triglyceride (TG) were the same among both men and women [13].…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, some studies have shown differences between men and women. In women, most risk factors for metabolic syndrome correlated with PWV, whereas no significance was found for these relationships in men [13,14]. For this study, we hypothesized that these differences are due to smoking, because there are many more male smokers than female smokers.…”
Section: Introductionmentioning
confidence: 87%
“…The main modifiable risk factor in the development of coronary artery disease is obesity, giving it a degree of cardiovascular risk similar to that associated with hypertension, hyperlipidemia, smoking and sedentarism 4 . Currently, the main treatments available to aid weight reduction are dietary guidance, the practice of supervised physical activity and the use of anti-obesity drugs.…”
Section: Introductionmentioning
confidence: 99%